The Logic of Qualitative Survey Research and its Position in the Field of Social Research Methods - Harrie Jansen (Forum: Qualitative Social Research, 2010)
Many qualitative studies describe the diversity of certain cognitions or behaviors in a population by means of semi-structured interviews with a small sample of population members. Up to now this type of qualitative research remains undefined in the methodological literature, however. It is argued that most of these studies may well be typified by the label "qualitative survey." While the statistical survey analyses frequencies in member characteristics in a population, the qualitative survey analyses the diversity of member characteristics within a population. The diversity of member characteristics may either be predefined or developed in open coding. Three levels of diversity analysis are defined: uni-dimensional description, multi-dimensional description and explanatory analysis, which may develop either in a concept-oriented or in a unit-oriented fashion. URN: urn:nbn:de:0114-fqs1002110